Frequência de neoplasia endócrina múltipla tipo 1 em pacientes portadores de adenomas hipofisários - Damianse, Sabrina da Silva Pereira (2016)
The multiple endocrine neoplasia type 1 (MEN1) is a genetic syndrome with autosomal dominant transmission, characterized by tumors of the parathyroid, anterior pituitary and pancreas. Primary hyperparathyroidism is the most common clinical presentation in MEN1 and evaluation of patients with pituitary adenomas for the presence of hyperparathyroidism could identify patients with this syndrome. The aim of this study was to identify the frequency of MEN1 by serum calcium and parathyroid hormone measurement in patients with pituitary adenomas followed at the Endocrinology Service of the Hospital Universitário da Universidade Federal do Maranhão (HUUFMA). This is a descriptive study with data collected from the patients' medical charts in june 2015 to may 2016. We evaluated 300 patients with pituitary adenoma subtypes (128 prolactinomas, 67 acromegaly, 22 corticotropinomas, 3 gonadotropinomas and 80 adenomas clinically nonfunctioning) finding a frequency of 1.3% of MEN1 patients among patients with adenomas pituitary. Patients with MEN1 were mostly female and the average age at diagnosis of pituitary adenoma was 42.7 years, ranging between 24 and 57 years old. Pituitary tumors of these patients were more often macroadenoma and the predominant subtype was somatotropinoma. At initial diagnosis, our patients had apparently sporadic pituitary lesions, however, or were confirmed with MEN1 early because they already have signs and/or symptoms of hyperparathyroidism, or have been diagnosed very late caused mild symptoms of parathyroid disease. Therefore, screening measures serum calcium and PTH in patients with pituitary adenomas are recommended, primarily, because these tests are necessary to identify the most common disease in MEN1, primary hyperparathyroidism. The study contributed to the identification of new patients with MEN 1 in those patients with pituitary adenomas with the benefit of early diagnosis, appropriate therapeutic approach and genetic counseling in family forms.